Diagnostic stewardship based on patient profiles: differential approaches in acute versus chronic infectious syndromes. Issue 11 (2nd November 2021) - Tiseo, Giusy; Arena, Fabio; Borrè, Silvio; Campanile, Floriana; Falcone, Marco; Mussini, Cristina; Pea, Federico; Sganga, Gabriele; Stefani, Stefania; Venditti, Mario
ABSTRACT: Introduction : New diagnostics may be useful in clinical practice, especially in contexts of high prevalence of multidrug-resistant organisms (MDRO). However, misuse of diagnostic tools may lead to increased costs and worse patient outcome. Conventional and new techniques should be appropriately positioned in diagnostic algorithms to guide an appropriate use of antimicrobial therapy. Areas covered : A panel of experts identified 4 main areas in which the implementation of diagnostic stewardship is needed. Among chronic infections, bone and prosthetic joint infections and subacute-chronic intravascular infections and endocarditis represent common challenges for clinicians. Among acute infections, bloodstream infections and community-acquired pneumonia may be associated with high mortality and require appropriate diagnostic approach. Expert opinion : Diagnostic stewardship aims to improve the appropriate use of microbiological diagnostics to guide therapeutic decisions through appropriate and timely diagnostic testing. Here, diagnostic algorithms based on different patient profiles are proposed for chronic and acute clinical syndromes. In each clinical scenario, combining conventional and new diagnostic techniques is crucial to make a rapid and accurate diagnosis and to guide the selection of antimicrobial therapy. Barriers related to the implementation of new rapid diagnostic tools, such as high initial costs, may be overcome through their rational and structured use.